Farmers' use of phone applications in accessing information for maize production in Kwara state, Nigeria - Olatinwo, Latifat Kehinde; Yusuf, Olayinka Jelili; Wahab, Munir Jamiu (Journal of Kerbala for Agricultural Sciences, 2024)
This study assessed the farmers' use of phone applications to access information for maise production in Kwara State. Data for the study were analysed using descriptive statistics, likert scale, and Pearson Product Moment Correlation (PPMC). A simple random sampling was used to select 120 maise farmers from 6 villages in both Omupo and Ajase-Ipo districts. The study revealed that 83.3% of the maise farmers were males with an average of 37.6, and 83.3% were married, with an average of 12 years of schooling. The average household size was 7 persons while the number of years of experience was 11 years. The study also revealed that the most common way of accessing information was through voice calls, radio, and WhatsApp, with all the respondents choosing both of these sources. The study also showed that poor internet networks on field/farm sites, with a mean score of 2.59 were the most glaring effect of the use of phones to access information on maise production, while the high cost of mobile smart/android phones with a mean score of 2.58 was one of the mitigating factors. The major constraint of using phone features/applications to access information was that smartphones use a bunch of data bundles and cost implications with a mean score of 2.61. The results of the hypothesis showed a significant relationship between socioeconomic characteristics and farmers' use of phone applications in accessing information for maise production. Data subscriptions on customised phones can also be made affordable for farmers.